Virtual Screening for Novel SarA Inhibitors to Prevent Biofilm Formation of Staphylococcus aureus in Prosthetic Joint Infections - Yu, Jinlong; Jiang, Feng; Zhang, Feiyang; Pan, Yunqi; Wang, Jianqiang; Han, Pei; Tang, Jin; Shen, Hao (Frontiers in Microbiology, 2020)
Staphylococcus aureus is one of the predominant causes of periprosthetic joint infections (PJIs). Bacterial adhesion and biofilm formation are important factors in the pathogenesis of PJIs. S. aureus biofilm formation is regulated by several factors, including S. aureus regulator A (SarA). Previous studies have found that SarA mutants have limited ability to develop biofilms. In this study, we identified a SarA-targeting antibiofilm compound, ZINC00990144, and evaluated its efficacy and toxicity. According to static biofilm assay, the antibiofilm ability of the compound was concentration dependent. ZINC00990144 reduced biofilm in multiple strains by 40 % to 86% at a concentration of 11.5 μM. Additionally, ZINC00990144 inhibited biofilm formation on different orthopedic implant materials including Titanium and UHMWPE disc. Furthermore, quantitative polymerase chain reaction results demonstrated that ZINC00990144 upregulated the expression of S. aureus exoproteases to inhibit the formation of biofilms. Moreover, ZINC00990144 prevented biofilm formation when exposed to sub-inhibitory doses of vancomycin, which is known to promote biofilm formation. CCK-8 results demonstrated ZINC00990144 has no significant effect on cell viability at concentration of 11.5μM or below. Finally, we verified the antibiofilm function of the compound in vivo using implant infection mice model with/without exposure to sub-inhibitory vancomycin. In conclusion, ZINC00990144 acts by modulating between biofilm and planktonic state of S. aureus instead of being bactericidal. Therefore, it has the potential to be used in combination with other antibiotics to prevent PJIs.